A comparison of soil characteristics from four land covers around a coal mining concession area in South Kalimantan - Yusanto Nugroho; Suyanto Suyanto; Gusti Syeransyah Rudy; Supandi Supandi; Yudha Hardiyanto Eka Saputra; Syamsu Alam; Jeriels Matatula; Pandu Yudha Adi Putra Wirabuana (Brawijaya University, 2022)
Understanding soil characteristics is important to determine the alternative strategies of land management, particularly those related to the scheme of soil and water conservation. This study investigated soil characteristics from four land covers around the coal mining concession area located in South Kalimantan. A soil survey was conducted using a purposive sampling method with three replicates in each land cover. Soil samples that were taken at depths of 0-10 cm, 11-20 cm, and 21-30 cm, were composited before being brought to the laboratory to quantify their characteristics, such as texture and organic carbon content. Data analysis was processed using a non-parametric test with a significant level of 5%. Comparison average of soil characteristics between land covers was evaluated using the Kruskal-Wallis test and followed by Nemenyi-test. Results found that soil characteristics from four land covers significantly differed in texture and organic carbon content. The highest sand fraction was noted in shrubs (67.23±0.86%), while the greatest silt fraction was recorded in plantation forests (29.71±2.84%). Compared to other land covers, the clay content in plantation forests and reclamation area was relatively equal by around 53-54%. On another side, The highest soil organic carbon was found in plantation forests with ranging of (4.44±0.14%) followed by natural forests (4.24±0.62%), shrubs (3.38±0.09%), and reclamation area (1.14±0.09%). These findings indicated there were high variations of soil characteristics from different land covers around the coal mining concession area. Therefore, it is recommended for managers to apply adaptive strategies in supporting soil conservation efforts based on the soil characteristics in each site.